Deviation Article 1320 against BW to provide legal protection in the agreement for Online Transportation - As Ari Arief Mamba (Fakultas Hukum Universitas Wahid Hasyim, 2022)
Article 1320 Boergerlijk Wetboek (BW) is the rule that gives signs an agreement validity that one of them stated that legal capacity as term of agreement In the theory, violation of the terms of this agreement may be canceled so achievements can still be implemented as long as there is no objection from the parties that incapacity to act in law. Problems of research not on whether or not the substance of the article May 1320 has been broken but the problem is the substance of the article into the text without meaning because the terms have been violated in the service agreement transport online, because maintaining legal capacity as agreement terms thus distancing the child from legal protection, especially in the transport agreement online. The research is the research of doctrinal. Based on the results of research on school-age children almost entirely using transportation services online by cellphone them